SELF-CONCEPT AND FAMILY SUPPORT AS THE FOUNDATION OF VOCATIONAL SCHOOL STUDENTS CAREER MATURITY - Pratomo, Shafa Aulia; Faslah, Roni; Wolor, Christian Wiradendi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
The purpose of this study was to find out how Self-Concept and Family Support affect Career Maturity among vocational high school students. The method used was a survey with a quantitative approach. The population studied included all 12th grade students at Public Vocational High School 50 Jakarta totaling 248 students. The sample was taken using proportional random sampling technique using the Slovin formula and a margin of error of 10%, resulting in a sample of 71 students. Data analysis was carried out using SmartPLS software version 4.0, including outer model analysis, inner model analysis, and hypothesis testing for direct effects. The results of the analysis showed that Self-Concept had a significant effect on Career Maturity. Meanwhile, Family Support also had a significant effect on Career Maturity. This study confirms that both Self-Concept and Family Support contribute positively and significantly to students' Career Maturity.